2001
DOI: 10.1182/blood.v97.1.264
|View full text |Cite
|
Sign up to set email alerts
|

Combined effect of all-trans retinoic acid and arsenic trioxide in acute promyelocytic leukemia cells in vitro and in vivo

Abstract: All-trans retinoic acid (tRA) and arsenic trioxide (As 2 O 3 ) induce non-cross-resistant complete clinical remission in patients with acute promyelocytic leukemia with t(15;17) translocation and target PML-RAR␣, the leukemogenic protein, by different pathways suggesting a possible therapeutic synergism. To evaluate this possibility, this study examined the effect of As 2 O 3 on tRA-induced differentiation and, conversely, the effect of tRA on As 2 O 3 -induced apoptosis. As 2 O 3 at subapoptotic concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
141
1
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 192 publications
(152 citation statements)
references
References 40 publications
9
141
1
1
Order By: Relevance
“…Previous studies have found that all-trans-retinoic acid increases Bcl2a1 mRNA levels and decreases apoptosis in the NB4 and PBL985 acute promyelocytic leukemia cell lines (55)(56)(57)(58). In a more recent study with PBL985 cells, 9-cis-retinoic acid increased Bcl2a1 expression but the RXR-selective agonist SR11237 did not (59).…”
Section: Discussionmentioning
confidence: 91%
“…Previous studies have found that all-trans-retinoic acid increases Bcl2a1 mRNA levels and decreases apoptosis in the NB4 and PBL985 acute promyelocytic leukemia cell lines (55)(56)(57)(58). In a more recent study with PBL985 cells, 9-cis-retinoic acid increased Bcl2a1 expression but the RXR-selective agonist SR11237 did not (59).…”
Section: Discussionmentioning
confidence: 91%
“…In addition to NFB, other transcription factors have been implicated in the transcriptional regulation of Bfl-1. These include all-trans retinoic acids in leukemia cells 401 , retinoic X receptor agonists in naïve T lymphocytes 402 , and the transcription factors WT-1 403 and PU.1 404 . On the other hand, Bfl-1 transcription has also been observed to be blocked by the transcription factor Blimp-1 in plasma cells 405 .…”
Section: The Regulation Of Bfl-1mentioning
confidence: 99%
“…29,58 Second, combination of the two agents allows a significantly prolonged survival or even disease eradication in APL animals. 63,64 Third, the two compounds target PML --RARa and modulate key networks involved in apoptosis/ differentiation via distinct but related pathways. 24,65,66 Mechanistically, the combined use of ATO with ATRA has brought about a conceptual revolution of synergistic targeting of leukemia and thus impacts the conventional chemotherapy-based treatment.…”
Section: Initial Approach For Suspected Aplmentioning
confidence: 99%